Modelling the establishment, spread and distribution shifts of pests - Lantschner, Maria Victoria; De La Vega, Gerardo; Corley, Juan Carlos (Taylor and Francis, 2023)
During the last century increasing human trade networks have interacted with other global changes – such as land use and climate change – to accelerate the range expansion of pest species worldwide. In this special issue, we present a series of articles that model the risk of establishment and spread of non-native harmful species, as well as shifts in the distribution of native pest species. We also provide a state-of the art review of the available literature on species distribution models for pests, weeds, and pathogens. Recent advances in modelling approaches have allowed us to significantly improve our abilities to predict changes in species distribution, and these tools have been widely used to enhance biosecurity planning and pest management. We expect that this special issue contributes toward and integration of the scientific knowledge and the development of novel approaches to model pest species distribution, as well as to better understand the factors that influence their expansion in the context of a rapidly changing world.